Antimicrobial susceptibility of coagulase-negative staphylococci isolated from red-tailed racers (Gonyosoma oxycephalum) - Men, Lydia Pow Kar; Noviana, Deni; Afiff, Usamah (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2022)
Antibiotic resistant coagulase-negative staphylococci (CoNS) have been reported around the world. The aim of this study was to determine the antimicrobial susceptibility of CoNS isolated from red–tailed racers. Samples were swabbed from the oral cavity of 5 wild caught red–tailed racers, and were identified with biochemical test using the Kirby–Bauer disc diffusion test interpreted by referring to Clinical and Laboratory Standards Institute. The results obtained 4 species of CoNS isolated from swab samples including S. sciuri, S. xylosus, S. lentus, and S. kloosii. The antibiotic resistance test of S. xylosus, S. sciuri, and S. lentus showed susceptibility to amoxicillin, gentamicin, erythromycin, bacitracin, vancomycin and oxacillin, but resistance towards penicillin G. S. sciuri isolated from snake number 1 was intermediate towards erythromycin. S. kloosii showed susceptibility towards amoxicillin, gentamicin, bacitracin, penicillin G, vancomycin, and oxacillin, but was resistant towards erythromycin